2013
DOI: 10.1093/infdis/jit290
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of West Nile Virus in Urine During Acute Infection

Abstract: Detection of West Nile virus (WNV) RNA in urine has been anecdotally described and proposed for the diagnosis of WNV infection. This study reports the routine use of real-time reverse-transcription polymerase chain reaction for the detection of WNV RNA in urine to support diagnosis of WNV infection during the large outbreak that occurred in northeastern Italy in 2012. Fourteen of 32 patients (43.8%) with symptomatic WNV infection, defined as neuroinvasive disease and fever, had detectable WNV RNA in urine at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
123
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(135 citation statements)
references
References 29 publications
10
123
0
2
Order By: Relevance
“…However, it is advantageous because of being non-invasive, and one study reported even higher sensitivity in testing [59]. Similar to other flaviviruses, urine may also be used to detect ZIKV RNA [93,94]. In fact, ZIKV may stay in the urine and remain positive for a longer duration than in the serum [51,58].…”
Section: Diagnosis Direct Viral Diagnosismentioning
confidence: 99%
“…However, it is advantageous because of being non-invasive, and one study reported even higher sensitivity in testing [59]. Similar to other flaviviruses, urine may also be used to detect ZIKV RNA [93,94]. In fact, ZIKV may stay in the urine and remain positive for a longer duration than in the serum [51,58].…”
Section: Diagnosis Direct Viral Diagnosismentioning
confidence: 99%
“…Diagnosis of other viral infections in urine and saliva samples has been reported for human immunodeficiency virus (HIV), Hepatitis A, B, and C, and rubella [14][15][16][17][18][19][20], and more recently in other flaviviruses, West-Nile virus (WNV) [21][22][23] and Dengue (DENV) serotypes -1, -2, -3, and -4 [24][25][26][27][28][29][30][31][32][33][34][35]. WNV can be detected longer in urine than serum [21] and can be isolated from urine [22,23].…”
Section: Advantages Of Non-invasive Sample Collectionsmentioning
confidence: 99%
“…WNV can be detected longer in urine than serum [21] and can be isolated from urine [22,23]. Some studies also suggest that like WNV, DENV can be detected for a longer time in urine than saliva or serum [25,29,31,32].…”
Section: Advantages Of Non-invasive Sample Collectionsmentioning
confidence: 99%
“…Therefore, the results should be interpreted with caution 37,38 . Urine samples for the detection of viral genomes by RT-PCR may be the diagnostic method of choice, since the disappearance of the genome in serum has been shown to be within 10 days for ZIKV, but in urine samples it can be detected until fifteen days after the onset of infection 58,59,60 (Table 2). Appropriate diagnostic specimens for RT-PCR testing include plasma/serum, urine, CSF, amniotic fluid and placental tissue.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Appropriate diagnostic specimens for RT-PCR testing include plasma/serum, urine, CSF, amniotic fluid and placental tissue. Serology is usually performed on serum; however, viral antibodies may also be detected in the CSF 58,59,60 .…”
Section: Diagnostic Methodsmentioning
confidence: 99%